Twenty years of experience with intraoperative pulmonary artery stenting. Issue 3 (4th May 2017) - Zampi, Jeffrey D.; Loccoh, Emefah; Armstrong, Aimee K.; Yu, Sunkyung; Lowery, Ray; Rocchini, Albert P.; Hirsch‐Romano, Jennifer C.
Abstract : Objectives: To describe our 20‐year experience with intraoperative pulmonary artery (PA) stent placement and evaluate long‐term patient outcomes, specifically the need and risk factors for reintervention. Background: Intraoperative PA stent placement is an alternative to surgical patch arterioplasty and percutaneous angioplasty or stent placement to treat branch PA stenosis. Methods: We performed a retrospective review of all intraoperative PA stents placed at our institution from 1994‐2013. Patient and stent characteristics and outcome data were collected. Risk factors associated with reintervention were identified using univariate cox regression analysis. Results: Eighty‐one PA stents were placed in 68 patients. The procedural complication rate was 4.4%. During a median follow‐up period of 6 years (interquartile range [IQR] 0.9‐12.7), 30 patients (44%) underwent reintervention on the stented PA with a median time to first reintervention of 2.6 years (IQR 0.7–4.4 years). The first reintervention was surgical in 30% and catheter‐based in 70%. Risk factors for reintervention included age < 18 months (Hazard ratio [HR] 2.97, P  = 0.005) and body surface area < 0.47 m 2 (HR 3.20, P  = 0.003) at the time of stent implantation, and the presence of multiple aortopulmonary collaterals in patients with tetralogy of Fallot (HR 4.61, P  = 0.003). Conclusions: Intraoperative PA stent implantation is a safe and effective alternative to percutaneous stent implantation and offers several advantages, including the ability to implant adult‐size stents in small patients while avoiding injury to peripheral vessels, to position stents to facilitate future percutaneous stent redilation, and to access the PAs directly, which eliminates radiation exposure. © 2017 Wiley Periodicals, Inc.